RAPID ASSESMENT LIMNOLOGIS SEBAGAI INDIKATOR PENGELOLAAN (REGULASI DAN PEMANFAATAN PERAIRAN) DI ZONA PENYANGGA LAHAN BASAH RESERVAT DANAU PANGGANG KABUPATEN HULU SUNGAI UTARA KALIMANTAN SELATAN - Pathul Arifin; Ardiannor Ardiannor; Dini Sofarini; Yunandar Yunandar (Faculty of Fisheries and Marine Resources of Lambung Mangkurat University-South Kalimantan, 2016)
The number of catches was declines in the water of the lake reservat Danau Panggang Hulu Sungai Utara of 2% per year from 3145.1 tons (2010) to 3030.0 tons (2013) and the presence of Lais fish (Cryptopterus Micronema) <1% annually followed by baung fish (Mystus nemurus) <0.5% that indicated decreased in water quality, productivity and aquatic environment as a whole as the ecological system.The purpose of the study (a) identify waters limnological conditions in the buffer zone area reservat Maningih; (B) analyze the spatial configuration of the activity at the location and values of the character bio-ecologist of aquatic resources; (C) assessed the overall condition of the attributes of the waters in the buffer zone; (D) Zoning map the profile to describe existing conditions at the sites.The methods of this research are analysis of the aquatic environment quality, as well as the biological index quissioner accompanied by descriptive statistics and mapping.A high concentration of organic material derived from organic waste with COD and level biodiversity indicators that is phytoplankton, is more dominant than zooplankton form Chlorophyta group as a manufacturer of natural fresh water to consumers in the formichtioplankton. The structure of the settlement at the location of the waters of 50-75%, cultivation and fishing as the main economic activities with the result of 2-10 species caught as well as four species whose presence is low. Mapping factors causing damage tothe buffer zone resulting from an increase of 30% residential, public behavior, intensity offishing and illegal fishing.